Globalization and the Internationalization of Adult and Higher Education: Challenges and Opportunities for Canada and the United States - Mary V. Alfred; Shibao Guo (Adult Education Research Conference, 2007)
The purpose of this study was to examine the extent to which adult higher education in Canada and the US was responding to the impact of globalization through the internationalization of research, curricular, and practice. Adult educators must be more deliberate in planning for a global civil society.